Melanoma and autoimmunity: spontaneous regressions as a possible model for new therapeutic approaches. Issue 3 (June 2019) - Motofei, Ion G.
Abstract : Until now, malignancy has been considered a cellular problem represented by the perturbed (uncontrolled) division of the cells associated with invasion and metastasis. Contrary to this classical approach, a new perspective suggests that cancerous disease is, in fact, a supracellular problem represented by inadequate evolution of complex supracellular processes (embryogenesis, development, regeneration, etc.). Such complex processes would be disconnected from the real needs of the body, inducing unnecessary or even dangerous events such as an exacerbated rate of the cell division, angiogenesis, immunosuppression (specific to embryogenesis and melanoma), invasion (mediated by trophoblastic/placental factors in melanoma), and migration (specific to neural crest cells, which generate melanocytes – the most common origin for melanoma). As a result, a correct and comprehensive interpretation of cancer (causes, evolution, therapy, and prevention) should be conducted from a supracellular perspective. After presenting the supracellular perspective, this article further investigates the favorable evolution of malignant melanoma in two distinct situations: in patients receiving no therapy and in patients treated with immune-checkpoint inhibitors. In patients receiving no therapy, spontaneous regressions of melanoma could be the result of several autoimmune reactions (inducing not only melanoma regression but also vitiligo, an autoimmune event frequently associated with melanoma). Patients treated with immune-checkpoint inhibitors develop similar autoimmune reactions, which are clearly correlated with better therapeutic results. The best example is vitiligo, which is considered a positive prognostic factor for patients receiving immune-checkpoint inhibitors. This finding indicates that immune-checkpoint inhibitors induce distinct types of autoimmune events, some corresponding to specific favorable autoimmune mechanisms (favoring tumor regression) and others to common unfavorable adverse reactions (which should be avoided or minimized). In conclusion, the spectrum of autoimmune reactions induced by immune-checkpoint inhibitors should be restricted in the near future to only these specific favorable autoimmune mechanisms. In this way, the unnecessary autoimmune reactions/autoaggressions could be avoided (a better quality of life), and treatment specificity and efficiency should increase (a higher response rate for melanoma therapy).